Information Technology Governance Audit In E-Learning using Cobit 2019 Framework (Case Study: Langlangbuana University Bandung) - Amelia Hani, .; Yiyi, Supendi (INTI International University, 2023)
To control the level of successful implementation of software, a governance audit is carried out using audit tools that are applicable in the community so that the audit results become a barometer for management in decision-making. With the development of technology and the existence of regulations issued by the Ministry of Education, Culture, Research and Technology that require distance learning (PJJ), the University of Langlangbuana Bandung requires PJJ to use self-developed E-Learning. In the implementation of E-Learning that is already running, a measurement is needed to determine the level of success. The tool that is widely used to conduct Information Technology Audits is COBIT 2019, which is the background for choosing a governance audit using COBIT because the implementation of international standard IT frameworks can produce measurements and recommendations for good IT management. IT governance by implementing the IT Framework is necessary so that technology performance can still be relied upon and optimal good governance. The audit results are expected to describe governance regarding policy implementation, Information Technology infrastructure, and services in the use of E-Learning using APO02-Manage Strategy, BAI09- Manage Asset, and DSS01-Manage Operation with the 2019 COBIT Framework. So that it can calculate the gap between the current capability level with the target capability level in ELearning. The final conclusion can provide recommendations to the management of Langlangbuana University in terms of managing strategy, managing assets, and managing operations as material for decision-making.